Edible oleogels for the oral delivery of lipid soluble molecules: Composition and structural design considerations. (November 2016) - O'Sullivan, Chloe M.; Barbut, Shai; Marangoni, Alejandro G.
Abstract: Background: Edible oleogels, oils structured by non-triglyceride networks, can be used for the delivery of lipid-soluble molecules due to their composition, functional properties, and structure. Different oleogelators exist, including small molecules that crystallize to form colloidal or fibrillar networks and hydrophobic polymers that self-assemble under specific processing conditions. Several types of edible oleogels have been characterized, but only select systems have been used in oral delivery applications. Scope and approach: This review covers the potential for use of edible oleogels for lipophilic molecular delivery. Factors affecting lipolysis relevant to oil gelation will be discussed, as well as the relationship between lipolysis and bioaccessibility. The use of lipid-based delivery systems to increase the bioaccessibility of poorly water-soluble molecules is emphasized, and oleogels are introduced as a delivery material. The review then discusses different methods of oleogelation, and addresses properties of oleogels that may be beneficial for delivery. Key findings and conclusions: Oleogel structure, mechanical strength, composition, and gelator type are factors that may affect the rate and extent of lipolysis of the material. These in turn affect the delivery of lipid-soluble molecules from the oleogel. Crystalline oleogels used in oral delivery formulations have been shown to offer increased bioaccessibility, prevention against bioactive recrystallization, and targeted or delayed bioactive release. In addition, the ability to manipulate oleogel physicochemical properties with gelator type, formulation, and processing parameters is beneficial for tailoring the material functionality. Ethylcellulose oleogels are unique food-grade polymer oleogels that could be used for delivery, similar to other crystalline oleogel systems. Graphical abstract: Highlights: Food grade crystalline and polymer oleogelators exist. Oleogel mechanical strength can be altered through composition and processing. Oleogel matrices can affect the rate of bioactive release. Oleogels can provide stability against bioactive recrystallization. Ethylcellulose oleogels are polymer-based and could be used for bioactive delivery.